Presence and distribution of dental enamel defects, recurrent aphthous lesions and dental caries in children with celiac disease - Cantekin, Kenan (Pak J Med Sci, 2015)
OBJECTIVE: To determine presence and distribution of enamel defects, recurrent oral aphthous lesions (RAS) and dental caries in children with Celiac Disease (CD) and compare the results with a healthy control group. METHODS: Twenty- five CD patients age between 4- 16 years with no other systemic disease, were examined in Pediatric Gastroenterology Clinic of Erciyes University, Faculty of Medicine (Kayseri, Turkey) and then referred to Department of Pediatric Dentistry, Faculty of Dentistry for dental examination and treatment. The control group (25 patients) consisted healthy patients referred to the Department of Pediatric Dentistry, Faculty of Dentistry, Erciyes University for restorative treatment. Both the CD group and control group was examined by the same investigator for the following; (1) enamel defects, (2) recurrent aphthous stomatitis, (3) dental caries. RESULTS: The mean dmft values for the CD group and control group were 3.25±3.25 and 4.56±2.87 respectively. The difference was not statistically significant.(P>0.05). The mean DMFT values for the CD and the control group were 3.75±2.62 and 1.83±1.7, respectively. There was a significant difference between the two groups (P<0.01). The prevalence of enamel defects and recurrent apthous stomatitis (RAS) was greater in celiac patients than in the control group. Enamel defects (in at least one permanent tooth) were observed in 12 out of 25 (48%) children in the CD group and four out of 25 children (16%).(P =0.01). Recurrent apthous stomatitis was found in 11/25 (44%) CD group, while no RAS was detected in the control group. CONCLUSION: Celiac Disease (CD) has adverse effects on oral health in term of enamel defect, recurrent aphthous stomatitis and caries score. Pediatricians and dentists especially pediatric dentists should be knowledgeable about oral symptoms of CD. Increased awareness can provide an early diagnosis and prevent long- term complications of this disease. On the other hand, further comprehensive investigations of CD patients can add to our understanding of the efficacy of CD on oral health in children.